Are the agrarian cooperatives possible? Shambillo’s experience from the implementation of an Alternative Development Project (ADP) - Hernando, Daniel (2019)
This article presents an analysis of the factors that favoured the transition of farmers in Shambillo from an illegal economy supported by the coca leaf to one based on the cultivation of oil palm in the framework of the intervention of an alternative development programme (PDA) which resulted in the creation of the Association of Palmiculturists of Shambillo (ASPASH). In Peru the successful experiences of agrarian organizations are few, the present work takes one of these cases and analyzes the factors that, from the perspective of the target public of the PDA, contributed to their functionig. This research argues that the risk experience with the cultivation of coca and the interest of local actors with prestige in being part of the PDA helped to overcome the mistrust and allowed the creation of ASPASH. After more than 15 years of foundation, we found a farming organization in the Amazon that has transformed the lives of its partners and that competes with other organizations and companies in the field of agroindustries in the Amazon. This article is a first approximation to understand the panorama of this type of projects and the factors that played in their implementation.